Animal models in HIV cure research - Luca Micci; Colleen S. McGary; Mirko Paiardini (Elsevier, 2015)
Current HIV antiretroviral therapy (ART) successfully inhibits viral replication in the majority of HIV-infected individuals. However, ART is not curative and lifelong adherence is required. Despite the undisputed benefit of ART, long-lived latently infected cells that carry HIV-integrated DNA remain. Hence, upon ART interruption, HIV-infected subjects experience viral rebound. Interestingly, similar disease course occurs in the well-characterised animal model of SIV-infected non-human primates. Using these animal models to investigate the mechanisms involved in the generation of latently infected cells, define the phenotypic and anatomical nature of persistent viral reservoirs, and test novel interventions for viral eradication, is critical for strengthening our understanding of HIV persistence and developing novel therapeutics aimed at curing HIV.In this review, we discuss the current animal models used in AIDS cure research, with a particular focus on non-human primates, and outline the experimental strategies explored in the quest for virus eradication.